1997
DOI: 10.1523/jneurosci.17-16-06463.1997
|View full text |Cite
|
Sign up to set email alerts
|

Stress and Dominance in a Social Fish

Abstract: Many aspects of reproductive physiology are subject to regulation by social interactions. These include changes in neural and physiological substrates of reproduction. How can social behavior produce such changes? In experiments reported here, we manipulated the social settings of teleost fish and measured the effect (1) on stress response as reflected in cortisol production, (2) on reproductive potential as measured in production of the signaling peptide, gonadotropin-releasing hormone, and (3) on reproductiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
186
4
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 266 publications
(202 citation statements)
references
References 42 publications
11
186
4
1
Order By: Relevance
“…In both sexes, nRnT individuals had higher serum cortisol than RT ones. In A. burtoni it was clearly demonstrated that nT males had more plasma cortisol levels than T ones, but this is also highly dependent on community conditions and length of time in these conditions (Fox et al, 1997;. In C. dimerus cortisol may serve as an endogenous signal relating the social environment to the social status of the animal, behavior and internal reproductive state.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In both sexes, nRnT individuals had higher serum cortisol than RT ones. In A. burtoni it was clearly demonstrated that nT males had more plasma cortisol levels than T ones, but this is also highly dependent on community conditions and length of time in these conditions (Fox et al, 1997;. In C. dimerus cortisol may serve as an endogenous signal relating the social environment to the social status of the animal, behavior and internal reproductive state.…”
Section: Discussionmentioning
confidence: 99%
“…There are strong interactions between behavior, the endocrine and nervous systems that affect the interactions between an animal and its environment, including social interactions. For example, dominance status has been shown to control fertility (Fraley & Fernald, 1982;Abbot et al, 1998;Faulkes & Bennet, 2001), suppressing gonadal maturation in subordinate individuals (Barret et al, 1990), and also influence on neurogenesis (Kozorovitskiy & Gould, 2004), growth rate (Hofmann et al, 1999), and stress (Fox et al, 1997;Abbot et al, 2003). Although social regulation on several physiological processes is a well-established phenomenon, little is known about the mechanisms linking the social environment to physiological changes associated with dominance.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the relationship of cortisol to social status in A. burtoni appears to depend not only on the status of the individual, but also on the social community and maturational state of the animals. For example, when males are housed in T-NT social pairs, GnRH neuronal soma size differences are significantly up-regulated in Ts vs NTs and differences in cortisol are statistically significant in older fish that lived as stable pairs for 2 weeks (Fox et al 1997). Among younger fish and in the first week of such pairings, cortisol levels were significantly more variable and showed only a trend towards higher values in NT males.…”
Section: Introductionmentioning
confidence: 98%